Metal-catalyzed plastic depolymerization - Khopade, Kishor V.; Chikkali, Samir H.; Barsu, Nagaraju (Cell Reports Physical Science, 2023)
Polymers have become an indispensable part of our daily lives, and today we produce around 370 MT of plastic per year. Only about 20% of it is being recycled, and the rest, 80%, is unleashed into the environment without appropriate treatment. This calls forth the evaluation of strategies available for mitigating the menace of ``after-use''plastic waste. Various approaches have evolved over a decade and are at different levels of development. Plastic depolymerization and upcycling are considered some of the most prominent and long-term solutions. The metal-catalyzed depolymerization of plastic waste to chemical feedstocks has emerged as one of the promising ways to address global plastic pollution. Therefore, this review aims to examine the available metal-catalyzed depolymerization methods, notify recent progress, pinpoint current gaps, and gauge the potential of this strategy. Both homogeneous and heterogeneous catalysts have been reported to depolymerize various polymers over the last decade. Considerable advances have been reported in the metal-mediated depolymerization of polyolefins, polyesters, polycarbonates, polyurethanes, polyamides, and polyethers. The depolymerization of the above polymers produces the monomers or intermediates, which can be used again for polymerization and thus brings the waste polymers back into circularity. The overview debates the usage of high temperaagents, etc., in metal-catalyzed depolymerization. Thus, this review summarizes the current understanding of the fundamental science of metal-catalyzed plastic depolymerization, the remaining scientific challenges, and the potential opportunities.